Kentucky's last cavalier : General William Preston, 1816-1887 - Sehlinger, Peter J. (Kentucky Historical Society, 2004)
"William Preston - politician, diplomat, and Confederate general - was the epitome of the antebellum southern landed aristocracy. Born to a well-to-do, well-connected Louisville family, the son of a Revolutionary War veteran, he was educated at Yale and Harvard and married the daughter of Kentucky's largest slaveholder."